Análisis de la contribución de Procompite en la mejora de la competitividad productiva en la Región Piura. Caso cadena productiva de panela granulada orgánica en el distrito de Montero, provincia de Ayabaca, 2014 – 2016 - Zegarra Cordova, Rony Ivan (2024)
The present research work is carried out as a contribution to improve the competitiveness in the production of granulated panela of the Piura Region, since with the approval of the National Policy of Competitiveness and Productivity - D.S. N°345-2018-EF, establishes that state institutions have the mission of implementing and executing competition and production policies and this to give greater emphasis to human resources, through skills and with the help of technology to generate a productive and associative environment (El Peruano, 2018). In addition, the implementation of PROCOMPITE in the north of Piura focused its attention on the sugarcane activity, which has the highest production in the Piura mountains, mainly in the provinces of Ayabaca and Huancabamba, which are producers of panela. The purpose of the research is to analyze the contribution that PROCOMPITE makes to improve the competitiveness of the production and marketing of organic granulated panela in the distric of Montero, province of Ayabaca in the Piura region, as well as the perceptions to implement proposals to improve the economy. The results obtained allow us to understand the successes and failures of PROCOMPITE Regional and contribute to the improvement of decision-making in a timely and efficient manner, based on the concepts of social management, guaranteeing that public investment has a positive and significant impact manifesting itself in the sustainable well-being of families.